Deciphering the maize gene ZmGF14–3: implications for plant height based on co-expression networks - Hengsheng Wang; Hengsheng Wang; Hengsheng Wang; Bo Wei; Lulu Qi; Lulu Qi; Yansong Chen; Yansong Chen; Kelong Chen; Dong Liu; Xu Su; Yan Zhang; et al. (Frontiers in Plant Science, 2024)
The evolutionary analysis showed that the GF14 family was conserved, however, there was limited evidence linking GF14s to plant height. In our investigations, we discovered a co-expression relationship between ZmGF14s and functionally characterized genes linked to plant height. In the co-expression network, we identified ZmGF14-3, a gene expression exhibiting a positive correlation with plant height in three maize varieties, we postulated that this gene could be intimately linked to plant height development. Subsequently, we cloned ZmGF14-3 from the maize B73 inbred line and overexpressed it in Arabidopsis, resulting in markedly dwarfed transgenic phenotypes. Measurements of endogenous phytohormones disclosed a significant reduction in concentrations of Gibberellic Acid 7 (GA7) and Indole-3-Acetic Acid (IAA) in the overexpressed Arabidopsis, furthermore, qPCR results highlighted a pronounced decrease in the expression levels of plant height-related genes when compared to the wild type, therefore, it is plausible to posit that ZmGF14-3 plays a pivotal role in regulating the growth and development of maize through interactions with various phytohormone-related genes. Thus, delving into the potential interactions between ZmGF14-3 and these genes holds the promise of yielding valuable insights into the molecular mechanisms underpinning plant height development in maize.